Strategies and Techniques for Building Confidence When Public Speaking for Beginners - Rahman, Rudi; Marzal, Novrizon (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
In this era, public speaking ability is a skill that a person must have. This ability is needed in academics, business, and other worlds. A public speaker┬áwith┬áhis role as an influence and benefit to┬álisteners┬áis required to┬áappear convincing. All his words, appearance, and behavior could be an inspiration for his listeners.┬áFor this reason,┬áthe element of┬ácommunication motivation must be inherent in a public speaker┬áin order to┬áavoid worries that make him doubt his abilities.┬áHowever, for beginners, public speaking is┬ásomething that is┬ádifficult to master, so you need to practice a lot and read several references related to strategies or techniques of public speaking itself, as explained in this article, which uses the Library Research method that aims to study texts, previous studies.┬árelated┬áto the topic┬ábeing discussed. The findings as an┬áimportant┬ápoint in this paper are that there are several strategies in public speaking, namely, Introduction to the Audience, Organizing material, Introduction to the place, and┬áPhysical appearance. Meanwhile, the techniques that beginners must master when public speaking┬áare:┬áIce Breaking┬áTechnique and Vocal TechniqueKeyword: Communication, Non Verbal, Analysis, Animated Series